Pesticide risk assessment in honeybees: Toward the use of behavioral and reproductive performances as assessment endpoints. (August 2021) - Barascou, Lena; Brunet, Jean-Luc; Belzunces, Luc; Decourtye, Axel; Henry, Mickael; Fourrier, Julie; Le Conte, Yves; Alaux, Cedric
Abstract: The growing gap between new evidence of pesticide toxicity in honeybees and conventional toxicological assays recommended by regulatory test guidelines emphasizes the need to complement current lethal endpoints with sublethal endpoints. In this context, behavioral and reproductive performances have received growing interest since the 2000s, likely due to their ecological relevance and/or the emergence of new technologies. We review the biological interests and methodological measurements of these predominantly studied endpoints and discuss their possible use in the pesticide risk assessment procedure based on their standardization level, simplicity and ecological relevance. It appears that homing flights and reproduction have great potential for pesticide risk assessment, mainly due to their ecological relevance. If exploratory research studies in ecotoxicology have paved the way toward a better understanding of pesticide toxicity in honeybees, the next objective will then be to translate the most relevant behavioral and reproductive endpoints into regulatory test methods. This will require more comparative studies and improving their ecological relevance. This latter goal may be facilitated by the use of population dynamics models for scaling up the consequences of adverse behavioral and reproductive effects from individuals to colonies. Highlights: There is a gap between new evidence of pesticide toxicity in honeybees and regulatory toxicological bioassays. Current endpoints should be complemented with behavioral and reproductive endpoints. We review such endpoints and discuss their possible use in pesticide risk assessment. There is a need to translate toxicological research studies into regulatory test methods.